2020
DOI: 10.1029/2020gl087348
|View full text |Cite
|
Sign up to set email alerts
|

Weakening of the Extratropical Storm Tracks in Solar Geoengineering Scenarios

Abstract: Solar geoengineering that aims to offset global warming could nonetheless alter atmospheric temperature gradients and humidity and thus affect the extratropical storm tracks. Here, we first analyze climate model simulations from experiment G1 of the Geoengineering Model Intercomparison Project, in which a reduction in incoming solar radiation balances a quadrupling of CO2. The Northern Hemisphere extratropical storm track weakens by a comparable amount in G1 as it does for increased CO2 only. The Southern Hemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…The increases in evapotranspiration due to overall warmer conditions can also play a role (not shown). The weakening and shifting of storm tracks (Gertler et al., 2020; Lee et al., 2021) and expansion of subtropical high‐pressure systems (Lin & Chan, 2015) in response to global warming could also favor the buildup of hot and dry conditions over land, which in turn dry out the soil and potentially increase wildfire occurrence (Figures S9 and S10 in Supporting Information ). Additionally, fire patterns in the midlatitudes are modulated by high latitude climate modes which have been projected to change with warming (Jain & Flannigan, 2021; Sato & Nakamura, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The increases in evapotranspiration due to overall warmer conditions can also play a role (not shown). The weakening and shifting of storm tracks (Gertler et al., 2020; Lee et al., 2021) and expansion of subtropical high‐pressure systems (Lin & Chan, 2015) in response to global warming could also favor the buildup of hot and dry conditions over land, which in turn dry out the soil and potentially increase wildfire occurrence (Figures S9 and S10 in Supporting Information ). Additionally, fire patterns in the midlatitudes are modulated by high latitude climate modes which have been projected to change with warming (Jain & Flannigan, 2021; Sato & Nakamura, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of SRMs aims to reduce the amount of incoming solar radiation reaching the surface: Stratospheric Aerosol Injection, Marine Cloud Brightening or Cirrus Cloud Thinning are among those strategies and some are already at the concept proof stage of their development (Tollefson, 2018). Recent studies highlighted the risks and the potential climatic feedback of some of those SRMs, with emphasis on major changes in storm track and storm intensity (Gertler et al, 2020), as well as on their social implications (Reynolds, 2019). Seneviratne et al (2018) while reviewing the main concerns raised by SRMs, concluded that climate engineering may indeed have a global impact but could lead to strong regional disparities and affect rainfall patterns.…”
Section: Solar Radiation Management Strategiesmentioning
confidence: 99%
“…Recent studies highlighted the risks and the potential climatic feedback of some of those SRMs, with emphasis on major changes in storm track and storm intensity (Gertler et al, 2020), as well as on their social implications (Reynolds, 2019). Seneviratne et al (2018) while reviewing the main concerns raised by SRMs, concluded that climate engineering may indeed have a global impact but could lead to strong regional disparities and affect rainfall patterns.…”
mentioning
confidence: 99%
“…These include forcing and feedbacks in response to SRM (Kashimura et al, 2017); SRM and CDR (Tilmes et al, 2016); Stratospheric ozone response to sulfate geoengineering (Pitari et al, 2014); Artic cryosphere response to sulfate geoengineering (Pitari et al, 2014); critical uncertainties for space-based solar geoengineering (Irvine et al 2010:1-6); albedo enhancement (Robock et al, 2016); precipitation seasonality (Bal et al, 2019); Greenland ice sheet (Moore et al, 2019); and Regional climate impacts (Jones et al, 2018) among others. Other designed GeoMIP experiments explored marine cloud whitening (Kravitz et al 2013), land and ocean albedo enhancement (Visioni et al, 2017); counter geoengineering (Heyen et al, 2015;; Precipitation response (Laakso et al, 2020); Weakening of the extratropical storm tracks (Gertler et al, 2020); mitigation of Arctic permafrost carbon loss (Chen et al, 2020) among others.…”
Section: Climate Geoengineering and The Srm Prospectsmentioning
confidence: 99%